Trait-space disparity in fish communities spanning 380 million years from the Late Devonian to present - John Llewelyn; John A. Long; Richard Cloutier; Alice M. Clement; Giovanni Strona; Frédérik Saltré; Michael S.Y. Lee; Brian Choo; Kate Trinajstic; Olivia Vanhaesebroucke; Austin Fitzpatrick; Corey J.A. Bradshaw (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Correction to: Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)

Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)
Trace DNA detection methods are increasingly applied to biomonitoring, in conservation, biosecurity, and wildlife forensic sciences. Reptiles are high risk invasive alien species that can cause damaging environmental impacts, yet the dynamics around terrestrial reptile DNA deposition and subsequent detection are poorly understood. Concerns around the role of the pet trade in introducing key reptile pests have resulted in calls for greater biosecurity surveillance and biomonitoring tools. Emerging studies have explored the applications of trace DNA and environmental DNA (eDNA) to reptile detectability, but questions remain around DNA persistence, sample storage, and DNA degradation through time influencing biosecurity compliance uptake. Here we consider Pantherophis guttatus (American corn snake), a key vertebrate pest species in Australia, as a model organism for the study of trace DNA detection over time. Our study focussed on the application of a recently developed corn snake LAMP assay for DNA detection from biosecurity relevant samples, with a particular focus on wildlife compliance for captive reptiles and shed skin samples subject to varied storage and environmental conditions. Experiments were conducted with (i) shed skin subject to a range of storage and treatment conditions over a 10-week period, (ii) trace DNA samples deposited on newspaper, plastic, glazed terracotta, and glass for 0 to 168 h post live snake presence, and (iii) shed skin samples subject to varying environmental conditions over an 8-week period. DNA remained detectable for up to 10 weeks under different storage conditions when extracted from shed skin and for up to 168 h after live reptile contact. DNA extracted from shed skin samples subject to varied environmental conditions was detectable up to 8-weeks post deposition with increasing times to detection. Our findings strengthen the case for trace DNA detection methods being applied to monitoring of terrestrial snakes, particularly for rapid compliance, monitoring, and environmental biosecurity.

The intersection of justice and urban greening: Future directions and opportunities for research and practice - Kate Derickson; Rebecca Walker; Maike Hamann; Pippin Anderson; Olumuyiwa Bayode Adegun; Adriana Castillo-Castillo; Anne Guerry; Bonnie Keeler; Liz Llewellyn; Austin Matheney; Nontsikelelo Mogosetsi-Gabriel; Seema Mundoli; et al. (Urban Forestry & Urban Greening, 2024)

Do plants matter?: Determining what drives variation in urban rain garden performance - Robyn Dudrick; Margaret Hoffman; Jalayna Antoine; Kate Austin; Laura Bedoya; Shirley Clark; Hannah Dean; Ann Medina; Sybil G. Gotsch (Ecological Engineering, 2024)

Biological Abundance and Diversity in Organic-Rich Sediments From a Florida Barrier Island Lagoon - Kate M. Fuller; Austin L. Fox; Charles A. Jacoby; John H. Trefry (Frontiers in Marine Science, 2021)
Organic-rich sediments in estuaries and the coastal ocean are often a product of land clearing, runoff of excess nutrients and other human activities. They can harbor pollutants, oxygen-consuming microbes and toxic hydrogen sulfide (H 2 S), thereby creating a hostile environment for infauna. In one barrier island lagoon, the Indian River Lagoon (IRL), Florida, layers of organic-rich sediments have increased substantially in thickness and areal extent over the past 60 years. Geochemical properties of these muddy sediments have been described; however, less is known about their habitability. We analyzed infauna and geochemical properties of 102 samples taken during wet and dry seasons at 17 locations spanning 60 km of the lagoon. We quantified infaunal abundance and diversity (Shannon-Wiener, H′) and determined Pearson’s correlation coefficients for effective number of species (ENS = e H ′) vs. sediment porosity (ϕ = 0.69–0.95), organic carbon (1–8%), nitrogen (0.1–0.7%), silt + clay (16–99%), porewater H 2 S (5–3,600 μM), and other environmental variables. Small bivalves accounted for 70% of the organisms collected, followed by gastropods, polychaetes and other biota. The bivalves were predominantly Macoma spp., Mulinia lateralis and Parastarte triquetra with average abundances of 3,896, 2,049, and 926 individuals per m 2 , respectively. High abundance of some species, such as Macoma , showed that these opportunists had adapted to poor quality sediments. More than two-thirds of the 35 species collected were present at <100 individuals per m 2 of sediment. Cluster analysis identified four groups of stations with significantly different geochemical properties. Permutation analyses of variance indicated that the four groups also represented statistically different infaunal communities. Diversity decreased with increasing sediment concentrations of organic carbon, nitrogen and silt + clay; however, community richness at our most prolific station along the perimeter of muddy deposits was ∼7 times lower than found previously in sandy sediments from the IRL. The results identified areas where infaunal communities have experienced the greatest stress due to accumulation of organic-rich sediments. Results from this study help support management plans for remediation of organic-rich mud and improvement of sediment and water quality, especially in areas identified with low ENS.

A Resilience Framework for Chronic Exposures: Water Quality and Ecosystem Services in Coastal Social-Ecological Systems - Nathaniel H. Merrill; Kate K. Mulvaney; David M. Martin; Marnita M. Chintala; Walter Berry; Timothy R. Gleason; Stephen Balogh; Austin T. Humphries (Coastal Management, 2018)

Xylene monooxygenase, a membrane-spanning non-heme diiron enzyme that hydroxylates hydrocarbons via a substrate radical intermediate - Rachel N. Austin; Kate Buzzi; Eungbin Kim; Gerben J. Zylstra; John T. Groves (JBIC Journal of Biological Inorganic Chemistry, 2003)